QD Framework - Using Dynamic Catalogs to Organize Mirror Servers on Scalable and Resilient Service Meshes - Pessoa, Gutenberg; Ramos, Daniel; Costa, Rostand; Duarte, Alexandre; Júnior, Jaelson; Griório, Francielly (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
In this paper we conceptualize and define the QD Framework, a generic solution to manage a set of mirror servers, enabling a specific online service to be offered on the web with a better availability and success rate for requests. The framework includes all the components needed to deal with such service: registration, cataloging, monitoring, distribution and access for the end users. For validation, a case study was done with an implementation of the proposed framework to support a large scale service that provides machine translation of digital content in portuguese language to LIBRAS (Brazilian Sign Language).